(3OjhGf EHQGgje GdYGedjs - (3EHQGgje Hf jMji Hf eMeO Hf SdjeGf GdeNRhej GdbQTj GdWjHj GdYGedj,J (B1214 (3g` s
(3ChdgG (B:s
(3CHGOJ edGbGg GdMQhH QLGdfG hYGT GdCYGOj Mjf eqdhG bJGdfG dCfG EPG QGe GdYOGI fRGdfG JbQH MH GdehJ CLGdfG dfG s
(3BNQgG (B:s
(3hjDLQ aj CLQ GdUGHQjf hef CMSf Gddg CLQg adG jNTGgG s
(3GdfSNI HgG MhGTs
(3Ydi ghGeT GdfSNI JYdjbGJ MOjKIs
(3hHBNQgG fbhd TYQjI hTQGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B75 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B127s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B12 s
Keywords: (3GdCOHs